Artificial Intelligence (AI) from the Perspective of Early Childhood Education as Social Beings and Person of Character - Doni Sudibyo; Sriayu; Nurteteng (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Early Childhood Education is a crucial foundation for a child's holistic development. This sector faces various challenges, including diverse individual needs, limited resources, and teacher qualifications. With the rapid advancement of Artificial Intelligence (AI), the question arises whether this technology can be an effective solution to overcome these obstacles. This journal explores the potential of AI in addressing ECE challenges, analysing both the opportunities and risks involved. We discuss how AI can support personalized learning, enhance accessibility, and alleviate the workload of educators. However, we also emphasize the importance of maintaining human interaction, data ethics, and mitigating bias. This journal concludes that while AI holds significant promise as a supportive tool, its implementation must be carried out carefully, integrated thoughtfully, and always prioritize the holistic development of the child.